The treasury single account as an institutional moderator in the interplay between fiscal revenue accretion and gross domestic product trajectories in Nigeria - Egbere Michael Ikechukwu; Tijjani Ahmed Ajayi (Yayasan Mitra Persada Nusantara, 2026)
This study investigates the Treasury Single Account (TSA) as an institutional moderator in the relationship between fiscal revenue accretion and Nigeria’s gross domestic product (GDP) trajectory. The aims are to evaluate whether TSA‐induced changes in revenue mobilization alter the strength and pattern of the revenue–GDP nexus, and to quantify any moderating effect across pre and post implementation periods. Using an ex post facto, longitudinal design, the study employs annual and quarterly data on federally collected oil and non oil revenues and GDP obtained from Central Bank of Nigeria, FIRS and NBS publications, covering pre TSA and post TSA eras. Analysis combines difference in means tests with moderated regression models interacting TSA status with disaggregated revenue components to capture institutional effects on growth responsiveness. Results are expected to show that, while aggregate revenue performance is mixed, TSA strengthens the positive association between non oil revenues and GDP, and stabilizes growth trajectories through enhanced transparency and cash management. The study concludes that TSA functions as a critical fiscal governance infrastructure, conditioning how revenue gains translate into macroeconomic performance.